2022
DOI: 10.3389/fnagi.2021.803080
|View full text |Cite
|
Sign up to set email alerts
|

Global Functional Connectivity Analysis Indicating Dysconnectivity of the Hate Circuit in Major Depressive Disorder

Abstract: BackgroundAbnormalities of functional connectivity (FC) in certain brain regions are closely related to the pathophysiology of major depressive disorder (MDD). Findings are inconsistent with different presuppositions in regions of interest. Our research focused on voxel-wise brain-wide FC changes in patients with MDD in an unbiased manner.MethodWe examined resting-state functional MRI in 23 patients with MDD and 26 healthy controls. Imaging data were analyzed by using global-brain FC (GFC) and used to explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Compared with HCs, MDD patients were reported to have increased ReHo values in the SMA (Liu et al, 2012;Yan et al, 2021). A previous study discovered significantly higher FC in SMA in MDD patients (Pan et al, 2021). Researchers in treatment-resistant MDD have shown that SMA hypometabolism had active response to antidepressant medication (Jiang et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Compared with HCs, MDD patients were reported to have increased ReHo values in the SMA (Liu et al, 2012;Yan et al, 2021). A previous study discovered significantly higher FC in SMA in MDD patients (Pan et al, 2021). Researchers in treatment-resistant MDD have shown that SMA hypometabolism had active response to antidepressant medication (Jiang et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the global functional connectivity density (gFCD) calculates the ratio of FC values to the voxels in different brain regions, eliminating the impact of differences in the brain area volume on FC ( Pan et al, 2022 ). The calculation method for local functional connectivity density (lFCD) is similar to that of gFCD, which represents the ratio of SC values to voxels in the brain regions ( Jia et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%